Persepsi karyawan terhadap implementasi konsep tri hita karana di sudamala suites & villas sanur, bali - Kusuma, I Wayan Adhitya; Ariana, I Nyoman Jamin; Putra, Agus Muriawan (Jurnal Kepariwisataan dan Hospitalitas; Vol 5 No 1 (2021): Vol.5,No.1,2021, 2021)
This study aims to determine employee perceptions of the implementation of the concept of Tri Hita Karana at Sudamala Suites & Villas Sanur. This research is descriptive qualitative & quantitative research. The sample in this research is using Saturation Sampling determination technique. The population referred to in this study are all employees (staff) Sudamala Suites & Villas who dujadikan the respondents a number of 70 people. Data collection techniques were conducted by observation, interview, questionnaires distribution, literature study and documentation.                The result of the research shows that employee perception towards the implementation of Tri Hita Karana concept in Sudamala Suites & Villas can be seen that from the three variables Tri Hita Karana has been categorized as well implemented with the total average score of 3.01, for Parhyangan get the average score 2,99, Pawongan variable got average score of 3.08, and variable of Palemahan get average score 2,96, this is because Sudamala Suites & Villas Sanur have implemented Tri Hita Karana concept but not yet fully. The result of this perception is in accordance with the opinion of the informant, Mr. Komang Satria Nugraha L. Putra as Asst. Human Resources Manager that the implementation of the Tri Hita Karana concept at Sudamala Suites & Villas has not been fully implemented due to several indicators of the unfinished Tri Hita Karana concept that caused Sudamala Suites & Villas Sanur to date have not been able to implement the concept of Tri Hita Karana.             The suggestions that can be submitted based on the results of the discussion is to improve the application of the concept of Tri Hita Karana by joining the Tri Hita Karana Awards & Accreditation competition, establishing a special Team as well as adding to the diversity of flora in Sudamala Suites & Villas so that the existing plant species do not look monotonous and look more beautiful and beautiful.